Appendicular Duplication – Variations in Anatomy and Associations: Appendicular Duplication - Md Asjad Karim Bakhteyar,; Ramjee Prasad ,; Digamber Chaubey,; Ramdhani Yadav,; Pranay Kumar,; Saurav ,; rahul, sandip kumar (Iranian Journal of Pediatric Surgery, 2023)
Background: Although Duplication anomalies are common in the Gastro-intestinal tract, appendicular anomalies are rare with variable anatomy. Objectives: To describe the series of appendicular duplication cases managed at a tertiary care center. Methods: Data regarding the clinical features, associated anomalies and management of cases of appendicular duplication at a tertiary care center from January, 2019 to December, 2020 were collected retrospectively and analyzed. Results: Four children with appendicular duplication were managed during this period; three neonates presented with high anorectal malformation and type two pouch colons with a large colovesical fistula. They had a single caecum with two separate appendices symmetrically on either side (type B1). They were managed by division of colo-vesical fistula, mobilization of colonic pouch after limited pouchoplasty and anoplasty as a single stage procedure. None of the appendix was removed. In one of these cases, bilateral ureters were dilated. The fourth case presented as a 3 year-old with pain abdomen and during surgery for suspected appendicitis, partial duplication of inflamed appendix was found (type A). Appendicectomy relieved this child of his symptoms. All patients are doing well on follow-up. Conclusion: The position, anatomy and associated anomalies of appendicular duplication can be variable complicating its presentation and management.